Autoimmunity in Focal Segmental Glomerulosclerosis: A Long-Standing Yet Elusive Association - Podestà, Manuel Alfredo; Ponticelli, Claudio (Frontiers in Medicine, 2020)
Focal segmental glomerulosclerosis (FSGS) is a histological term that describes a pathologic renal entity affecting both adults and children, with a wide array of possible underlying etiologies. Podocyte damage with scarring, the hallmark of this condition, leads to altered permeability of the glomerular barrier, which may result in massive proteinuria and relentless renal function deterioration. A definite cause of focal segmental glomerulosclerosis can be confirmed in a minority of cases, while most forms have been traditionally labeled as primary or idiopathic. Despite this definition, increasing evidence indicates that primary forms are a heterogenous group rather than a single disease entity: several circulating factors that may affect glomerular permeability have been proposed as potential culprits, and both humoral and cellular immunity have been implicated in the pathogenesis of the disease. Consistently, immunosuppressive drugs are considered as the cornerstone of treatment for primary focal segmental glomerulosclerosis, but response to these agents and long-term outcomes are highly variable. In this review we provide a summary of historical and recent advances on the pathogenesis of primary focal segmental glomerulosclerosis, focusing on implications for its differential diagnosis and treatment.